Long-term safety and efficacy of pegvaliase for the treatment of phenylketonuria in adults: combined phase 2 outcomes through PAL-003 extension study - Nicola Longo (Orphanet Journal of Rare Diseases, 2018)
Abstract Background Deficiency of phenylalanine hydroxylase causes phenylketonuria (PKU) with elevated phenylalanine (Phe) levels and associated neuropsychiatric and neurocognitive symptoms. Pegvaliase (PEGylated phenylalanine ammonia lyase) is an investigational agent to lower plasma Phe in adults with PKU. This study aimed to characterize the long-term efficacy, safety, and immunogenicity of pegvaliase in adults with PKU. Methods PAL-003 is an ongoing, open-label, long-term extension study of the pegvaliase dose-finding parent phase 2 studies. Participants continued the dose of pegvaliase from one of three parent studies, with dose adjustments to achieve a plasma Phe concentration between 60 and 600 μmol/L. Results Mean (standard deviation [SD]) plasma Phe at treatment-naïve baseline for 80 participants in the parent studies was 1302.4 (351.5) μmol/L. In the 68 participants who entered the extension study, plasma Phe decreased 58.9 (39)% from baseline, to 541.6 (515.5) μmol/L at Week 48 of treatment. Plasma Phe concentrations ≤120 μmol/L, ≤360 μmol/L, and ≤ 600 μmol/L were achieved by 78.7, 80.0, and 82.5% of participants, respectively. Mean (SD) protein intake at baseline was 69.4 (40.4) g/day (similar to the recommended intake for the unaffected population) and remained stable throughout the study. All participants experienced adverse events (AEs), which were limited to mild or moderate severity in most (88.8%); the most common AEs were injection-site reaction (72.5%), injection-site erythema (67.5%), headache (67.5%), and arthralgia (65.0%). The AE rate decreased from 58.3 events per person-year in the parent studies to 18.6 events per person-year in the extension study. Conclusions Pegvaliase treatment in adults with PKU produced meaningful and persistent reductions in mean plasma Phe concentration with a manageable safety profile for most subjects that continued with long-term treatment. Trial registration ClinicalTrials.gov, NCT00924703. Registered June 18, 2009, https://clinicaltrials.gov/ct2/show/NCT00924703